Preschool Child Nutritional Status in Nepal in 2016 and Comparative Trends (P11-074-19). (13th June 2019) - KC, Angela; Thorne-Lyman, Andrew; Shrestha, Binod; Manohar, Swetha; Webb, Patrick; West, Keith P
Abstract: Objectives: Estimate the national and agro-ecological zonal prevalence of preschool child undernutrition and review temporal trends in the prevalence of undernutrition. Methods: In 2016, we conducted the last in a series of 3 (also 2013 and 2014) nationally representative, annual, same-season, mixed-longitudinal nutrition surveys – PoSHAN Community Studies – in the same 21 Village Development Committees sampled across the Mountains, Hills and Tarai of Nepal. Height/length and weight measurements of 5479 children < 5 years were converted to z-scores of height-for-age (HAZ) and weight-for-height (WHZ) based on World Health Organization growth standards. Cut-offs of < -2 z-scores of HAZ and WHZ were applied to define stunting and wasting, respectively. Rates of stunting and wasting were compared to four Demographic and Health Surveys of Nepal (NDHS) from 2001–2016. Annual rates of decline in stunting and wasting were calculated. Results: Preschool stunting and wasting rates from PoSHAN in 2016 were 34% [95% CI: 29.5 to 38.9%] and 13.7% [11.0 to 16.9%], similar to those observed in the 2016 NDHS: 35.8% [33.5 to 38.3%] and 9.7% [8.4 to 11.1%], respectively. Stunting was highest in the Mountains (40.6%), and wasting in the Tarai (18.9%). PoSHAN surveys revealed an annual decrease in the prevalence of stunting of 1.5% from 2013–2016 and 2.3% from 2011–2016, representing a lesser decline than in the earlier period of 2001–2011 (3.3%) (Figure 1 a). In contrast, neither series of surveys has revealed a marked decline in the national prevalence of wasting over the past 15 years (Figure 1 b). Conclusions: The rates of stunting and wasting seen in the PoSHAN survey were comparable to other contemporary surveys in 2016 and suggest that the current rate of decline is inadequate to meet Nepal's 2025 World Health Assembly (WHA) target of reducing stunting to 26.5%. However, wasting has changed very little, threatening the potential to reach Nepal's national WHA target of 5%. Funding Sources: Funded by USAID Feed the Future Nutrition Innovation Lab, with assistance from Sight and Life and The Gates Foundation. Supporting Tables, Images and/or Graphs: